EXPERIENTAL LEARNING BERBASIS KEARIFAN LOKAL DALAM PEMBELAJARAN BAHASA JERMAN DI SMAN 3 TUAL - Tomasouw, Jolanda; Lestuny, Carolina; Akihary, Wilma; Soumokil, Piet (Universitas Pattimura, 2024)
The use of a good learning model is instrumental in creating enjoyable learning. Fun learning can produce active, creative and interactive student attitudes. German language learning based on local wisdom using experiental learning model aims to (1) measure the extent of the contribution of experiental learning model in German language learning (2) measure students' knowledge about local wisdom in their own area (3) increase students' participation in the German language learning process in class. This research is a descriptive qualitative research type. The samples used in this study were students of class XI of SMAN 3 Tual, Southeast Maluku. Data were obtained through instruments such as questionnaires, interviews and worksheets. First, students were given a questionnaire before the research which contained statements about the situation of German language learning, including experiental learning components and local wisdom; second, the researcher analyzed the problems encountered in the learning process through the results of student questionnaires; third, students were given an experiental learning model by incorporating local wisdom in the German language learning process; Fourth, students are given worksheets that are done in groups and present the results of work using the station lernen method; Fifth, students are given a questionnaire after the implementation of the experiental learning model; Sixth, data processing is carried out to see the results of the implementation of experiental learning models based on local wisdom in German language learning; and seventh, drawing conclusions on the results of data processing. The results obtained from this study are by applying experiental learning in German language learning, it can contribute to students in the learning process. Students are actively involved and share experiences based on what they get and experience